"Being a Teacher is Somehow Marked by Contradictions Somewhere": A Longitudinal Study of Subjective Theories on Teaching in Inclusive Classrooms (Pedagogical Horizons, 2020)
Subjective theories guide perception and action and influence how teachers plan, teach and reflect. Therefore, they are crucial for professionalization. This paper examines how the subjective theories of teacher students concerning teaching in inclusive classrooms change during a seminar. The students' subjective theories were collected at four points in time with the help of structure formation maps and problem-oriented interviews. The analysis shows that subjective theories differentiate and new concepts are integrated. However, new concepts are sometimes described by the students as contradictory to existing concepts. Here, the students' tolerance of ambiguity proves to be extremely significant: the better the students are able to deal with contradictions, the less they tend to resolve the contradictions and the more positive their attitudes towards inclusive teaching are.
Keywords: Tolerance of Ambiguity; Subjective Theories; Structure Formation Technique; Teaching in Inclusive Classrooms